KOMUNIKASI PARTAI POLITIK BARU SEBAGAI PESERTA PEMILIHAN UMUM LEGISLATIF TAHUN 2019: STUDI DPD PARTAI SOLIDARITAS INDONESIA KABUPATEN KATINGAN - Hendra Pitika; Imanuel Jaya (Jurusan Ilmu Pemerintahan, 2018)
This study aims to find out how New Political Party Communications as Participants Legislative Election Year 2019 (Study DPD Indonesian Solidarity Party Katingan regency). The method used in this research using qualitative research method with descriptive approach. Based on this research, it is known that the Regional Leadership Board of Indonesian Solidarity Party (DPD PSI) of Katingan Regency uses all political communication as the election participants in 2019 in Katingan Regency which is an indicator in the writing of this thesis, ie political communicator as information giver containing political weight , political messages in the form of election law and party, political channels or media in the form of means in conveying the intent and purpose of the party to the public, the target or target in the form of community support in terms of voting, as well as political influence or effect in the form of the result of communications made to the party the. With the stipulation of the Regional Leadership Council of the Indonesian Solidarity Party (DPD PSI) of Katingan Regency as the legislative election participants in 2019, through the verification stages made by Katingan District Election Commission (KPU) which is the success as a new political party, politics that brought change to Katingan Regency, by really fighting for the aspirations of society through its legislative legislative cadres. Thus, as a new political party with stewardship dominated by young people can bring prosperity for the people of Katingan Regency. Keywords: Communication of the new Political Party, as a participant of legislative election